PEERS’ ANATOMY: teaching among students as an original approach to learning anatomy – a project made in Alma Mater - Pergolizzi, Carola; Toscano, Fabrizio; Broccoli, Alessandro; Orsini, Ester; Quaranta, Marilisa; Mariani, Giulia Adalgisa (Italian Journal of Anatomy and Embryology, 2015)
Anatomy is an ancient discipline which benefited greatly from technological improvements. Those very same technologies, along with a shift towards more clinically relevant topics, might be endangering anatomy’s central role as a cornerstone of medical education. A review of local realities showed anatomy to be quite uniformly taught by means of lectures alone. On the basis of our own experience, and comforted by references in literature (Day et al. [1]), we propose a revaluation of the teaching approach to anatomy, which includes an integration between different available resources and, above all, introduces peer-to-peer activity. Over the course of the last decade, based on a proposal from the Anatomy Department, more and more medical students took part to gross anatomy workshops abroad, thus consolidating what today is a large group of tutors. Working in parallel with the lectures, back home these students organize activities where notions are not a mere tool to pass the exam, but are aimed at giving younger students solid foundations on which to build their future competence. On the grounds of the experiences acquired in these years, we managed to divide the tutoring activities into six areas: surface and topographic anatomy, muscles and skeleton, heart and thorax, neuroanatomy, abdomen and pelvis, didactic coordination. Each group is based on the equal division of tasks and on respecting each tutor’s expertise, attitudes and skills. These workshops have proved to be highly effective both for students, as a chance to experience anatomy “hands-on”, and for tutors, as an opportunity of mastering the subject. Being appointed a tutor outlines a shift from a deductive learning method, typical of the pre-exam phase, to an inductive one, more useful in the future as medicine doctors. To sum up, the availability of adequate facilities for cadaveric dissection certainly enhances the teaching of anatomy; what our experience shows, however, is that only direct involvement of students as tutors brings out the full potential of these activities. We therefore propose abandoning a pure “learning-to-do” approach, in favour of a more effective “learning-by- doing” strategy.